How do Australians use social media during natural hazards? A survey. (15th October 2022) - Zander, Kerstin K.; Sibarani, Rifka; Lassa, Jonatan; Nguyen, Duy; Dimmock, April
Abstract: People living in Australia are highly exposed to risks from extreme weather events including floods, bushfires and tropical cyclones. Communication is crucial in emergencies, to prepare for risks, warn people, reduce impacts, save lives and increase resilience. Social media has become increasingly important for both sourcing and disseminating information during natural hazards. The vast amount of data generated by social media users can be analysed for situational awareness, impacts and community sentiments during natural hazards. The full potential for social media to fulfil these roles in Australia is not yet well understood. In this study, we provide a literature review about the use of social media during natural hazards in Australia. We then assess public preferences for the use of social media during natural hazards using data collected through an online survey (n = 1665). Results suggest that social media is still largely underutilised for emergency communication. However, those with a high capacity to prepare for emergencies were more likely to use social media during natural hazards than those who relied on decisions being made by local authorities. Respondents' age did not explain the use of social media during natural hazards, but gender did with women more likely to do so than men. The presence of children in a household increased the use of social media during natural hazards, suggesting that the family structure plays a role in disaster communication. Finally, the main barriers to using social media during natural hazards were the spread of conflicting information and rumours on social media.